Living fabrication of functional semi-interpenetrating polymeric materials - Zhuojun Dai (Nature Portfolio, 2021)
Cell based materials production has potential for generating diverse materials with a range of functions. Here, the authors report development of living fabrication of biohybrid semi interpenetrating polymer networks by encapsulating protein producing bacteria within polymer microcapsules.